2018
DOI: 10.1108/mrr-04-2017-0128
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of eWOM on the customer purchase intention through value co-creation (VCC) in social networking sites (SNSs)

Abstract: Purpose The purpose of the study was to investigate the effect of electronic word of mouth (eWOM) on the value co-creation (VCC) and purchase intentions of consumers in Facebook fan pages of smartphone brands in India. Design/methodology/approach The data were collected using a structured questionnaire from a sample of 762 members from India present in the selected fan pages of smartphone brands in Facebook, and the data were analyzed through structural equation modeling. Findings This empirical study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 95 publications
(98 reference statements)
1
44
0
9
Order By: Relevance
“…According to the second attribute, E-WOM affected the consumer purchase intention, related to the second sub-hypothesis this result is similar with the derived results from other studies (e.g. Kazmi & Mehmood, 2016;Kunja & GVRK, 2018) which operated on the same field of smartphones via other variables, such as "value co-creation", "brand image and product type" and brand image respectively. This is similar to some studies (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…According to the second attribute, E-WOM affected the consumer purchase intention, related to the second sub-hypothesis this result is similar with the derived results from other studies (e.g. Kazmi & Mehmood, 2016;Kunja & GVRK, 2018) which operated on the same field of smartphones via other variables, such as "value co-creation", "brand image and product type" and brand image respectively. This is similar to some studies (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…At the same time, eWOM messages are deemed a very essential reference as it assists consumers to determine their purchasing decision-making processes (Chan & Ngai, 2011;Park et al, 2007;Sohaib et al, 2018). Previous studies found a significant positive influence between eWOM and consumers PI (Kunja & GVRK, 2018) which indicated the effect of eWOM on value co-creation and purchase intention, in that, positive comments, posts, and shares through consumers on social media improve purchase decision making and purchase intention. Reza Jalilvand and Samiei (2012) also studied the significant impact of eWOM communication on purchase intention and brand image.…”
Section: Ewom and Pimentioning
confidence: 97%
“…Word of Mouth (WOM) has been one of the most important channels of communication in information exchange among consumers (Chan & Ngai, 2011;Chu & Kim, 2011;Kim et al, 2014;Kunja & GVRK, 2018;Richins, 1984). It can significantly affect attitudes and consumer behavior and is also considered as one of the key marketing tools (Avery et al, 1999;Chen & Xie, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…From adverse selection and quality uncertainty frameworks [3][4][5], this paper utilizes consumers' reliance on eWOM as a reasonable behavior to reduce information asymmetry and uncertainty in e-commerce. On the basis of social engagement and social risk frameworks, eWOM variables such as valence (review rating) and volume can be understood as crucial factors to reduce social risk and information asymmetry affecting product sales [6], purchasing intentions or decisions [7,8], product imagery [9] or brand attitudes [10]. Further, the usefulness, or helpfulness, of online reviews has been considered to be important, as helpfulness can affect the relationship between eWOM and product sales [6,11].…”
Section: Introductionmentioning
confidence: 99%